Influence of grit and healthy lifestyle behaviors on anxiety and depression in US adults at the beginning of the COVID-19 pandemic: Cross-sectional study - Mike Toczko; Justin Merrigan; Ali Boolani; Bishop Guempel; Italia Milani; Joel Martin (Tabriz University of Medical Sciences, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic altered lifestyles and impacted mental health of many adults. Engaging in physical activity, avoiding prolonged sitting, and consuming a healthy diet improve mental health. The current study investigated the association between health-related lifestyle behaviors on feelings of anxiety and depression in adults during the early stages of the COVID-19 pandemic. Methods: Adults (n=796) living in the United States completed an internet-based survey in Spring 2020 that included validated survey instruments for moods, physical activity, sitting and dietary behaviors. Multivariate multiple regression models were used to assess the association between health-related lifestyle behaviors and feelings of anxiety and depression. Results: A majority (70.7%; 95% CI: [0.607, 0.807]) of participants met physical activity (PA) guidelines, 43.7% (95% CI: [0.287, 0.587]) sat for ≥ 8 hours per day, and 87.7% (95% CI [0.807, 0.947]) ate a healthy diet. Our final models explained 6.2% and 9.8% of the variance in anxiety and depression, respectively. Vigorous PA (anxiety: B=-0.111, 95% CI: [-0.171,0.000]; depression: B=-0.111, 95% CI: [-0.186,-0.037]) and dietary behaviors (anxiety: B=-0.112, 95% CI: [-0.180,-0.444]; depression: B=-0.112, 95% CI: [-0.213,-0.076]) were associated with reduced feelings of anxiety and depression while sitting time (anxiety: B=0.119, 95% CI: [0.000,0.199]; depression: B=0.119, 95% CI: [0.199,0.199]) were associated with greater feelings of anxiety and depression. Conclusion: Engaging in vigorous physically activity, reducing sitting time, and consuming a healthy diet was associated with reduced feelings of anxiety and depression during the early part of the pandemic. The aforementioned modifiable lifestyle behaviors are independent of each other suggesting improvements in one behavior may improve feelings of anxiety and depression.